Utilization of Sustainable Livelihood Assets in the Development of Tourism Villages in Labuan Bajo, West Manggarai Regency - Inayah, Nurul; Prayitno, Gunawan; Adrianto, Dimas Wisnu (Syntax Corporation, 2026)
Labuan Bajo is one of the villages located in Komodo District, West Manggarai Regency, East Nusa Tenggara Province. This area is known as the gateway to Komodo National Park, which is the natural habitat of the Komodo dragon, one of Indonesia's ancient animals. Labuan Bajo has become a magnet for tourists from around the world thanks to its stunning natural beauty, from exotic beaches and small islands to extraordinary underwater riches. This study aims to provide an understanding of the value of sustainable livelihoods, which will ultimately facilitate the formulation of recommendations for better development and management in the tourist village of Labuan Bajo. The human dimension shows a fairly good score (59.83), indicating that community involvement and capacity are beginning to take shape, although there is still a need for improvement in terms of skills and management. The dimension with the lowest score is finance (35.75), which indicates significant weaknesses in terms of funding, investment, and distribution of economic benefits. This situation makes finance the most vulnerable aspect, which could hinder sustainability if not addressed immediately. Given these weaknesses, it is hoped that future research will expand the variables, adopt more diverse data collection methods (such as in-depth interviews or longitudinal secondary data), and increase the number and distribution of samples to obtain more complete and accurate results.